E) -7(x-2)=3x-1
F) 4(x-1)=6(1+x)


Odpowiedź :

[tex]e) \: - 7(x - 2) = 3x - 1 \\ - 7x + 14 = 3x - 1 \\ - 7x - 3x = - 1 - 14 \\ - 10x = - 15 \: \: | \div ( - 10) \\ x = 1.5[/tex]

[tex]f) \: 4(x - 1) = 6(1 + x) \\ 4x - 4 = 6 + 6x \\ 4x - 6x = 6 + 4 \\ - 2x = 10 \: \: | \div ( - 2) \\ x = - 5[/tex]

Odpowiedź:

-7(x-2)= 3x - 1

-7x + 14 = 3x - 1

-7x - 3x = - 14 - 1

-10x = - 15/ :(-10)

x= 1 i 5/10 , czyli 1 i 1/2

4(x-1)= 6(1 + x)

4x - 4 = 6 +6x

4x - 6x = 4+6

-2x= 10/ :(-2)

x = - 5

Szczegółowe wyjaśnienie:

Mam nadzieję, że dobrze . Ale np 1 i 1/ 2 to jedna cala i jedna druga , no bez tego i sie pisze ale nie wiedziałam jak zapisać